Administering anticipatory medications in end-of-life care: A qualitative study of nursing practice in the community and in nursing homes. (January 2015) - Wilson, Eleanor; Morbey, Hazel; Brown, Jayne; Payne, Sheila; Seale, Clive; Seymour, Jane
Background: In the United Kingdom, an approach to improving end-of-life care has been the introduction of 'just in case' or 'anticipatory' medications. Nurses are often responsible for deciding when to use anticipatory medications, but little is known about their experiences. Aim: To examine nurses' decisions, aims and concerns when using anticipatory medications. Design: An ethnographic study in two UK regions, using observations and interviews with nurses working in community and nursing home teams ( n = 8). Findings: Observations ( n = 83) and interviews ( n = 61) with community nurses. Nurses identified four 'conditions' that needed to be established before they implemented anticipatory medications: (1) irreversibility; (2) inability to take oral medication; (3) where the patient was able, they should consent and (4) decision had to be independent of demands or requests from patient's relatives. By using anticipation medications, nurses sought to enable patients to be 'comfortable and settled' by provision of gradual relief of symptoms at the lowest dose possible. They aimed to respond quickly to needs, seeking to avoid hospital admission or medical call-out, while adhering to local prescribing policies. Worries included distinguishing between pain and agitation, balancing risks of under- and over-medication and the possibility of hastening death. Conclusion: Nurses take a leading role in the administration of anticipatory medications. Nurses apply consideration and caution to the administration of anticipatory medications but some experience emotional burden. Education, training and experience played a role in the nurses' confidence and should continue to be central to efforts to improving the quality of palliative care in the community and nursing homes.